My first love and other disasters - Pascal, Francine (New York : Simon Pulse, 2003)
Victoria Martin falls in love with the most popular boy in school, but her attempts to win him over end in disaster.
Young Adult
Keywords: Man-woman relationships -- Juvenile fiction; Schools -- Juvenile fiction; Teenage girls -- Juvenile fiction; Man-woman relationships -- Fiction; Schools -- Fiction; Teenage girls -- Fiction; Girls -- Fiction; Man-woman relationship -- Fiction; School stories; Teenagers -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction